2009
DOI: 10.1186/1297-9686-41-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the number of markers per haplotype and clustering of haplotypes on the accuracy of QTL mapping and prediction of genomic breeding values

Abstract: The aim of this paper was to compare the effect of haplotype definition on the precision of QTL-mapping and on the accuracy of predicted genomic breeding values. In a multiple QTL model using identity-by-descent (IBD) probabilities between haplotypes, various haplotype definitions were tested i.e. including 2, 6, 12 or 20 marker alleles and clustering base haplotypes related with an IBD probability of > 0.55, 0.75 or 0.95. Simulated data contained 1100 animals with known genotypes and phenotypes and 1000 anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 25 publications
2
55
1
1
Order By: Relevance
“…An additional difference between marker AIS and IBD haplotypes is that the IBD status of haplotypes is evaluated at one position in the genome (a so-called putative QTL position), whereas AIS haplotypes are considered to be AIS across the whole haplotype. When IBD probabilities between two haplotypes are close to one, those haplotypes are usually considered to be the same to reduce the number of effects that needs to be estimated and thereby increasing power to estimate effects (Yu et al, 2005) and speeding up convergence (Calus et al, 2009). …”
Section: Genome -Wide Breeding Value Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional difference between marker AIS and IBD haplotypes is that the IBD status of haplotypes is evaluated at one position in the genome (a so-called putative QTL position), whereas AIS haplotypes are considered to be AIS across the whole haplotype. When IBD probabilities between two haplotypes are close to one, those haplotypes are usually considered to be the same to reduce the number of effects that needs to be estimated and thereby increasing power to estimate effects (Yu et al, 2005) and speeding up convergence (Calus et al, 2009). …”
Section: Genome -Wide Breeding Value Estimationmentioning
confidence: 99%
“…Apart from a few methods that assume equal contribution to the genetic variance by all loci, a common feature of these methods is to reduce the dimension of the SNP data. Reported alternatives include non-parametric kernel methods (Gianola et al, 2006;Bennewitz and Meuwissen, 2008;Gianola and van Kaam, 2008), partial least squares (PLS) regression Solberg, 2008), principal component analysis (PCA; Solberg, 2008), genetic algorithms, and Bayesian LASSO (de los Campos et al, 2009). Kernel methods were shown to yield similar results as the Bayesian methods for purely additive models (Bennewitz and Meuwissen, 2008), but may outperform the Bayesian models when considering non-additive effects (Gonzá lez- Recio et al, 2008).…”
Section: Genome -Wide Breeding Value Estimationmentioning
confidence: 99%
“…Examples are estimation of breeding values in livestock to enable genomic selection (Meuwissen et al, 2001), or prediction of the (genetic) susceptibility of an individual for a disorder or disease (Wray et al, 2007). Generally, the applied models for both types of GWA studies may be the same, although fine-tuning for one of both objectives may result in subtle differences in the applied models (Calus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to the RHM would be to cluster the haplotypes on the basis of their origin. The clustering could be based on IBD probabilities where haplotypes with very high IBD probability are clustered together (Blott et al, 2003;Sahana et al, 2008;Calus et al, 2009) or it could be based on genealogy (tree-based) (Pan et al, 2009). Such clustering may also be used in combination with the RHM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g. Zhao et al, 2007;Becker and Herold, 2009;Calus et al, 2009) compared power of haplotype-based models for QTL mapping, but did not compare type I errors. Sahana et al (2010) observed a very high type I error rate using haplotype as a fixed effect in the model.…”
mentioning
confidence: 99%